Lean or obese, the epicardial fat thickness is increased in diabetics of south India – is it a south Indian paradox?. (14th October 2021) - Rameshwar, R; Meenakshi, K; Gowrishankar, A
Abstract: : Type 2 Diabetes Mellitus (T2DM) is considered a Coronary Artery Disease (CAD) risk equivalent (1) Increased epicardial fat (EFT) thickness is one hypothesis contributing to the disproportionate CV morbidity and mortality in T2DM (2). Studies have shown, EFT was higher in patients T2DM and high BMI compared to the non diabetic group. (3). The aim of our study was to determine if T2DM patients had an increased EFT thickness even when their BMI was normal or low and whether there was a relation between the T2DM duration and the EFT thickness. Study cohort consisted of 260 patients, who underwent coronary angiography (CAG) for suspected CAD. All patients underwent detailed history, examination, routine biochemistry, HBA1c, Anthropometric measurements such as weight, height, waist circumference and BMI. Transthoracic ECHO assessment of EFT was done one day prior to CAG using the ECHO unit with a 3.6MHz transducer. The EFT thickness was measured as the echo-free space between the myocardium and visceral pericardium on the right ventricular free wall in end-systole in the parasternal long and short-axis views for 3 cardiac cycles. CAG was performed in the fasting state, using the Judkins' technique, by the femoral or radial artery approach. The severity of CAD was assessed by modified Gensini scoring system. The collected data were analysed with IBM.SPSS statistics software. Of the 260 patients 90 (73.1%) were males and 70 (26.9%) were females. In this study, the average value for normal EFT was 5.2mm in the control group (HBA1c <7) and anything more than 6 was taken as abnormal. Patients were divided into 4 groups based on their HbA1c levels viz Group A (HbA1c <7), Group B (HbA1c 7–9), Group C (HbA1c 9.1–12) and Group D (HbA1c >12). The EFT increased with increasing HbA1c levels and the correlation was statistically significant P value 0.0005. There was no gender differences in EFT in our study. EFT was higher when the T2DM duration was >5 yrs which was statistically significant. p value 0.0005 (Table 1). There have been no reports of the correlation between the duration of DM and EFT in literature to the best of our knowledge.There was a strong correlation between HbA1c and EFT and the severity of the coronary lesions which was statistically significant. There was no correlation between the BMI and EFT or CAD (Figure 1) and the EFT was increased even in non obese diabetics. This may be due to the fact that EFT is a part of visceral obesity whereas BMI is a measure of generalised obesity. Our study showed a linear correlation between EFT thickness, HBA1c, duration of T2DM irrespective of BMI values confirming the recent thinking that regional fat depots such as EFT are of greater importance as a CAD risk factor than overall adiposity as was previously considered. ECHO measured EFT can be used to raise the clinical suspicion of CAD in asymptomatic diabetics and being non invasive can also be used for followup. Funding Acknowledgement: Type of funding sources: None.